Mechanistic assessment and ablation of left ventricular assist device related ventricular tachycardia in patients with severe heart failure - Hohendanner, Felix; Bock, Matthias; Keznickl-Pulst, Julian; Furundzija, Vesna; Scholz, Sebastian; Schöppenthau, Doreen; Hrytsyna, Yuriy; Falk, Volkmar; Pieske, Burkert; Hindricks, Gerhard; Potapov, Evgenij; Gerds-Li, Jin-Hong (Frontiers in Physiology, 2023)
Aims: Left-ventricular-assist-devices (lvad) are an established treatment for patients with severe heart failure with reduced ejection fraction (HF) and reduce mortality. However, HF patients have significant substrate for ventricular tachycardia (VT) and the lvad itself might be pro-arrhythmogenic. We investigated the mechanism of VT in lvad-patients in relation to the underlying etiology and provide in-silico and ex-vivo data for ablation in these HF patients. Methods and Results: We retrospectively analyzed invasive electrophysiological(EP) studies of 17 patients with VT and lvad. The mechanism of VT was determined using electroanatomical, entrainment and activation time mapping. Ischemic cardiomyopathy was present in 70% of patients. VT originated from the lvad region in >30%. 1/6 patients with VT originating from the lvad region had episodes before lvad implantation, while 7/11 patients with VT originating from other regions had episodes before implantation. Number and time of radiofrequency(RF)-ablation lesions were not different between VTs originating from the lvad or other regions. Long-term freedom from VT was 50% upon ablation in patients with VT originating from the lvad region and 64% if ablation was conducted in other regions. To potentially preemptively mitigate lvad related VT in patients undergoing lvad implantation, we obtained in-silico derived data and performed ex-vivo experiments targeting ventricular myocardium. Of the tested settings, application of 25 Watt for 30 sec was safe and associated with optimal lesion characteristics. Conclusion: A significant percentage of patients with lvad undergoing VT ablation exhibit arrhythmia originating in close vicinity to the device and recurrence rates are high. Based on in-silico and ex-vivo data, we propose individualized RF-ablation in selected patients at risk for/with lvad related VT.